Gestational Diabetes-Mellitus and it’s Associated Risk-Factors Among Women at an Antenatal Clinic at a Tertiary-Care Hospital Of Rawalpindi - Sultan, Nadia; Azam, Naila; Javed, Qaisar; Raza, Fatima Ali; Abid, Sana (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the frequency of GDM and its associated risk factors at an antenatal outpatient department at Fauji Foundation Hospital in Rawalpindi. Study Design: Cross sectional study. Place and Duration of Study: Gynecology and Obstetrics outpatient department Fauji Foundation Hospital, Rawalpindi, Pakistan Nov 2021 to May 2022. Methodology: Our study was done on 330 gravid females (gestational age between 24-30 weeks) aged 20-45 years who were selected by purposive sampling. Women with pre diagnosed diabetes mellitus type II and depression were excluded from the study. Fasting blood glucose sample of participants was taken at their 24-30 weeks visit followed by the OGTT according to the modified International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria. BMI, MUAC and blood pressure were taken at their booking antenatal visit. International physical activity questionnaire (IPAQ) was used for history of physical exercise during pregnancy. MDDS scoring was used for dietary diversity. Results: The mean age of the sample at time of study was 31.95 (SD±6.34) years. A total of 330 pregnant women participated, of which 47(14.2 %) were GDM positive. GDM was positively associated (p<0.05) with BMI greater than 30, MUAC greater than 28 cm, no exercise, antenatal depression, familial history of GDM and DM, pregnancy induced hypertension (PIH) in current pregnancy, past account of pregnancy with GDM, and bad obstetrics history. Conclusion: The positive predictors of GDM were familial GDM, low physical activity and obesity. Incorporating healthy life style and dietary modifications along with regular screening during pregnancy are recommended